Impact of Neuropathy on Well-Being and Health-Related Quality of Life in Adolescents With Type 1 Diabetes - Vinni Faber Rasmussen; Mathilde Thrysøe; Páll Karlsson; Jens Randel Nyengaard; Kurt Kristensen; Esben Thyssen Vestergaard (Journal of Diabetes Research)
Conclusion: In conclusion, adolescents with diabetic autonomic neuropathy who also reported autonomic symptoms had lower well-being and impaired social inclusion. Adolescents with symptoms of neuropathy and females appear to be at higher risk of lower well-being, and using standardized screening tools helps to identify the subjects at risk.